Grafting biomaterials associated to topical glucocorticoid: effects on pre-osteoblastic cells (MC3T3-E1) - Alice de Araújo Ferreira SILVA; Carolina Nemesio de Barros PEREIRA; Danilo Rocha DIAS; Frederico Santos LAGES; Katia Lucy Melo MALTOS; Allyson Nogueira MOREIRA; Elton Gonçalves ZENÓBIO; Ivana Márcia Alves DINIZ (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract The topical glucocorticoid budesonide has been prescribed before and after sinus lift surgery as adjuvant drug treatment for maxillary sinus membrane inflammation. However, there is no study on the effects of budesonide on the regenerative process of bone grafting biomaterials. We investigated the effect of the association of budesonide with some biomaterials on the growth and differentiation capacity of pre-osteoblastic cells (MC3T3-E1 subclone 4). Xenogeneic (Bio-Oss and Bio-Gen) and synthetic hydroxyapatites (Osteogen, Bonesynth, and HAP-91) were tested in conditioned medium (1% w/v). The conditioned medium was then supplemented with budesonide (0.5% v/v). Cell viability was assessed using the MTT assay (48, 96, and 144 h), and mineralized nodules were quantified after 14 days of culture using the Alizarin Red Staining. Alkaline phosphatase activity was assessed through the release of thymolphthalein at day seven. All biomaterials showed little or no cytotoxicity. The Bio-Gen allowed significantly less growth than the control group regardless of the experimental time. Regarding differentiation potential of MC3T3-E1, the HAP-91-conditioned medium showed remarkable osteoinductive properties. In osteodifferentiation, the addition of budesonide favored the formation of mineral nodules when cells were cultured in medium conditioned with synthetic materials, whereas it weakened the mineralization potential of cells cultured in xenogeneic medium. Regardless of whether budesonide was added or not, Osteogen and Bio-Oss showed higher alkaline phosphatase activity than the other groups. Budesonide may improve bone formation when associated with synthetic biomaterials. Conversely, the presence of this glucocorticoid weakens the mineralization potential of pre-osteoblastic cells cultured with xenogeneic hydroxyapatites.